The Effectiveness of Puzzle Therapy in Improving the Cognitive Function of the Elderly - Freny Ravika Mbaloto; Estelle Lilian Mua; Robi Adikari Sekeon; Denny Susanto; Ida Yanriatuti; Sabarulin Tarigan; Juliana Neng Rifka Sarman; Nova Natalia Beba (STIKES Adi Husada, 2023)
Mild cognitive impairment is a term for people who are at risk of developing dementia. Cognitive decline is an elderly perspective that is commonly a health problem because it is closely related to physical health, psychological health, and quality of life in the elderly. This study aimed to determine the effect of puzzle therapy on the cognitive function of the elderly. This type of quantitative research is pre-experimental with a one-group pretest-posttest design approach. The population in this study was 24 elderly people, using a saturated sampling technique. The intervention carried out was puzzle therapy given for 30-60 minutes over a period of 1 week. Puzzle therapy is a fragment of several images from a complete picture that is designed to stimulate the brain so that the brain's cognitive role increases. The cognitive abilities of the elderly were measured using the MMSE (Mini-Mental State Examination) questionnaire in the form of a test consisting of 30 points of cognitive function including orientation, registration, attention and calculation, remembering, and language. Score 24-30 (good cognitive function), score 1-23 (cognitive impairment). hypothesis analysis using the Wilcoxon test. The results of the study showed that the puzzle therapy variables influence the cognitive abilities of the elderly (p.value 0.01). To improve the cognitive function of the elderly, it can be done through scheduled puzzle therapy in the daily activities of the elderly.